An Optimized Path Planning for Wheeled Robot in Obstacle Environments - Mohamed Amine Yakoubi; Djamel Bektache; Abderahmane Gaham; Raouf Toumi (IEEE explore, 2021)
In this paper, we have proposed an obstacle avoidance algorithm for a path planning in unknown environment for a mobile robot based on the fuzzy logic control. Therefore, the wheeled mobile robot is equipped with 3 wheels, one steering wheel and two fixed wheels and mounted on the same axis. Its task is to move from a starting position to a target position. For this, our proposed algorithm creates one or more imaginary target and applies a fuzzy logic control system, which is adopted by a rule table that is induced from two inputs data (the distance and the angle between the robot and the target) and two outputs data (the angle orientation and velocity of the steer wheel). Experimental results show the effectiveness of the proposed algorithm.